PENGARUH EFEKTIFITAS PELATIHAN DAN DISIPLIN KERJA SERTA LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA DAN KINERJA KARYAWAN PT. ADIRA DINAMIKA MULTI FINANCE TBK JEMBER - Fatoni, Imam (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract : This study aims to analyze the effect of the effectiveness of training and discipline and work environment on performance through employee morale at PT. Adira Finance in Jember. The variables in this study include X1 = effectiveness of the training, X2 = labor discipline, X3 = work environment as independent variables, Z = morale as an intervening variable and Y = performance as the dependent variable. The method of data analysis is the analysis of the path (path analysis) with a significance level (Î±) = 5%. Testing was conducted by using the classical assumption test and test hypotheses. The sample in this study amounted to 50 people. This study used a technique stratitifed proportionate random sampling (random sampling proportionally according to the stratification). The results show the effectiveness of training (X1), labor discipline (X2), and the work environment (X3), has a significant effect on morale (Z), the effectiveness of training (X1), labor discipline (X2), and the work environment (X3), has a significant effect on performance (Y), and morale (Z) has a significant effect on performance (Y). Keywords: Effective Training, Labor Discipline, Work Environment, Performance, and Morale.